Pengembangan Jiwa Kepemimpinan dan Kemandirian Ekonomi pada Masyarakat di Era Digital di Yayasan Tajaul Karomatu Desa Situ Gadung Kabupaten Tangerang - Laveny Citra Nurhayati; Muhammad Andika Rahmat Kurniawan; Refky Restoe Pradiska; Wawan Supriyatna (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid advancement of digital technology has created both opportunities and challenges for communities in developing leadership capacity and achieving economic independence. In the digital era, individuals are required to possess adaptive leadership skills and entrepreneurial competencies to improve their welfare and organizational performance. Therefore, community empowerment programs are needed to enhance these capabilities among educational institution personnel. This Community Service Program (PKM) aimed to develop leadership spirit and strengthen economic independence among teachers and staff of Yayasan Tajaul Karomatu, Situ Gadung Village, Tangerang Regency. The activity was conducted on August 31, 2025, at Yayasan Tajaul Karomatu by three lecturers from Universitas Pamulang. A total of 20 participants, consisting of teachers and foundation staff, attended the program. The implementation method included material presentations, practical exercises, discussions, and question-and-answer sessions. The PKM activities were carried out through three stages: preparation, implementation, and reporting. The results showed that participants gained a better understanding of leadership concepts, digital-era challenges, and strategies for achieving economic independence. Participants demonstrated increased motivation to improve leadership skills, utilize digital technology productively, and explore entrepreneurial opportunities. The interactive learning approach also encouraged active participation and knowledge sharing among participants. Overall, the program contributed positively to enhancing leadership awareness and economic self-reliance within the foundation community.